2018
DOI: 10.32473/edis-pp338-2018
|View full text |Cite
|
Sign up to set email alerts
|

Rose Mosaic Virus Disease: A Disease Caused by a Virus Complex and Symptoms on Roses and Management Practices

Abstract: Rose mosaic virus disease is one of the most economically important diseases affecting roses, because a single symptomatic leaf can result in the rejection of complete shipments for wholesale or retail rose producers. It continues to be a problem in nursery production and landscapes. This 5-page document discusses the causes, symptoms, and management of this disease. Written by Susannah da Silva, Binoy Babu, Mathews L. Paret, Gary Knox, Fanny Iriarte, Barron Riddle, Matt Orwat, Shawn T. Steed, E. Vanessa Campo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…For all the diversity of viral symptoms, many of them are similar to those caused by other pathogens which makes diagnosis difficult (Figure 2). Based on the articles by various authors, it may be concluded that the most typical and common manifestation of the viral diseases affecting Rosa L. plants is viral mosaic caused by such pathogens as Prunus necrotic ringspot virus, Apple mosaic virus and Arabis mosaic virus [8,39,41,[61][62][63][64][65]. Its hallmark is that the infection has a mono-or mixed nature, that is, it is triggered by a single virus or a group of viruses.…”
Section: Banded Chlorosis Wrinkling; Malformation and Chlorotic Spots...mentioning
confidence: 99%
See 3 more Smart Citations
“…For all the diversity of viral symptoms, many of them are similar to those caused by other pathogens which makes diagnosis difficult (Figure 2). Based on the articles by various authors, it may be concluded that the most typical and common manifestation of the viral diseases affecting Rosa L. plants is viral mosaic caused by such pathogens as Prunus necrotic ringspot virus, Apple mosaic virus and Arabis mosaic virus [8,39,41,[61][62][63][64][65]. Its hallmark is that the infection has a mono-or mixed nature, that is, it is triggered by a single virus or a group of viruses.…”
Section: Banded Chlorosis Wrinkling; Malformation and Chlorotic Spots...mentioning
confidence: 99%
“…Its hallmark is that the infection has a mono-or mixed nature, that is, it is triggered by a single virus or a group of viruses. Moreover, manifestations of one or several viruses may be different: chlorotic lines; ringspots; vein clearing and banding; leaf mottling during vegetation; yellow netting and yellow mosaic; oak leaf pattern; leaf distortion and curling; necrosis; flower distortion; flower size reduction; shrinkage in the plant stem at the grafting point [24,26,63,64].…”
Section: Banded Chlorosis Wrinkling; Malformation and Chlorotic Spots...mentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms associated with RMD are highly variable, depending primarily on rose cultivars, virus agents and environmental factors. Some of the common foliar symptoms include chlorotic line patterns, ring spots, yellow vein banding and puckering, intense yellow spots, mottling and severe distortion [10]. In addition, flower distortion, reduced flower production and flower size, stem caliper at the graft union and reduction in vigor, early autumn leaf drop, lower bush survival rates, increased susceptibility to cold injury and more difficult establishment after transplanting are shown.…”
Section: Introductionmentioning
confidence: 98%